(untitled) (Journal of Guidance and Counselling Studies, 2024)
This study investigated the correlation between secondary school students’ self-efficacy and their academic achievement in Imo State. Five research questions were answered, and two hypotheses were tested at 0.05 level of significance. Correlation research design was adopted for this study. The population for this study consisted of 8,463 Senior Secondary School (SS2) students. Research sample consisted of 860 (420 male and 440 female) students selected through multi-stage sampling technique. The instrument used for the study was Morgan-Jinks Student Self-efficacy Scale (MJSES) which has coefficient alphas of .78, .70 and .66 for subscales, and an overall reliability coefficient of .80. Data collected for the study were analysed using summated scores descriptive statistics, Pearson Product Moment Correlation and Regression analysis. Results obtained from the study indicated that a good number of students in Imo state have high academic self-efficacy. The result also showed that a good number of the students in Imo state have good achievements in English language and mathematics. Finally, the result revealed that there is significant positive relationships secondary school students’ Self-efficacy and their academic achievement in English Language and Mathematics respectively. The study recommended, among others that Counsellors, teachers and other staff should create programmes that will help develop strong belief in the self-capacity.